Neural Bases of Age-Related Sensorimotor Slowing in the Upper and Lower Limbs - Marusic, Uros; Peskar, Manca; De Pauw, Kevin; Omejc, Nina; Drevensek, Gorazd; Rojc, Bojan; Pisot, Rado; Kavcic, Voyko (Frontiers in Aging Neuroscience, 2022)
This study aimed to investigate age-related differences in sensorimotor processes in the upper- and lower-limbs using event-related potentials (ERPs) and a simple visual reaction task (RT). Strength (amplitudes) as well as timing and speed (latencies) of various stages of stimulus- and motor-related processing were analyzed in 48 healthy individuals (young adults, n=24, mean age=34 years; older adults, n=24, mean age=67 years). The behavioral results showed a significant age-related slowing, where younger compared to older adults exhibited shorter RTs for the upper- (222 vs. 255ms; p=0.006, respectively) and the lower-limb (257 vs. 274ms; p=0.048, respectively) as well as lower variability in both modalities (p=0.001). Using ERP indices, processing of visual stimuli was characterized by overall larger amplitudes with delayed latencies of endogenous potentials in older compared to younger adults. While no differences were found in the P1 component, the N1 amplitude showed greater negative deflection in old compared to young adults for both, upper- and lower-limbs (p<0.01). The P2 component was affected by age with larger and delayed peak amplitudes in both limbs (p<0.05). The analysis of motor-related cortical potentials (MRCPs) revealed stronger MRCP amplitude for upper- (p=0.002) and a trend for lower-limbs (p=0.097) in older adults. The MRCP amplitude was larger for lower- compared to upper-limb in both age groups (p<0.001). The MRCP peak latency occurred earlier for lower- as compared to upper-limb in younger (p<0.001) and older adults (p=0.004). There were longer MRCP onset latencies for lower- as compared to upper-limb in younger (p<0.001) and a trend in older adults (p=0.095). While in older adults, upper-limb RT was additionally predicted by MRCP rise time and P2 latency, the overall RTs were predicted by the MRCP onset latency parameter. Our study shows that age-related slowing of upper- and lower-limbs is not influenced by early processes of visual stimulus processing but has its origin in motor-related processes and partly in endogenous processes. This process most likely reflects a less efficient depolarization process of the neurons for the upper and lower extremities in older adults.